Kajian Perdagangan Internasional dan Pertumbuhan Ekonomi: Peran Strategis Nilai Tukar dan Inflasi di Indonesia - Rezki Apri Zulharji Siswanto; Dewi Mahrani Rangkuty; Bakhtiar Efendi (Journal of Economics Research and Policy Studies, 2026)
In the era of economic globalization, international trade has become a key factor in shaping a country’s economic growth dynamics. Through export and import activities, a country can expand its markets, improve production efficiency, and obtain goods and services that cannot be produced domestically at optimal levels. This study was conducted to examine the effects of exports, imports, and international trade policies, assess the impact of exchange rates and inflation, and examine the role of tax policies in Indonesia’s economic growth. The study covers the period from 1995 to 2024 and employs a quantitative research approach, using multiple linear regression. The variables tested include exports, imports, tariffs, import duties, exchange rates, inflation, and taxes relative to GDP. Research data were sourced from various providers, including the Central Statistics Agency (BPS), Bank Indonesia, and the World Bank. The results indicate that exchange rates and inflation have a significant negative impact, while the other variables are not statistically significant when analyzed individually. These findings underscore the importance of macroeconomic stability and the synergy of trade, monetary, and fiscal policies in supporting sustainable economic growth.